(untitled) (Research, Society and Development, 2022)
Breast cancer is the type of neoplasm that most affects the Brazilian female population. With regard to treatment, chemotherapy corresponds to the use of drugs intravenously or orally. However, the chemodynamics and kinetics of pharmacological treatments, can affect the quality of life of patients. Face do, it was sought from sought to carry out a treatment of quality data, which were studied from the main patients to Rita and which were studied from the main patients to Rita. Maringá-PR. Therefore, an epidemiological study was carried out with analysis, descriptive and exploratory cross-sectional, which used, for data collection, the instrument of the group European Organization for Research and Treatment of Cancer - EORTC, QLQ-BR23. As for the results obtained, there are no symptoms, the problems that they obtained were the problems that the patients obtained and were considered in relation to the expected results, this means the two most serious points that the patients were diagnosed with. In addition, compared to the first group achieved among patients in the adjuvant regimen, the worst result to sexual pleasure, obtained a significant difference (p = 0.055). When comparing the results obtained with other research as well as the international treatment, it was possible to observe that the national way is different for each patient and each aspect of their quality of life.